Antidepressant efficacy of sertraline and imipramine for the treatment of major depression in elderly outpatients - Forlenza,Orestes Vicente (2000)
CONTEXT: Most double-blind studies of efficacy and tolerability of sertraline as compared to tricyclics in the treatment of late-life major depression have used amitriptyline as a standard, leading to the inevitable conclusion that the former drug is better tolerated than the latter, with both being equally efficacious. OBJECTIVE: To compare the antidepressant efficacy and tolerability of sertraline (50 mg/day) and imipramine (150 mg/day) in the first 6 weeks of the treatment of major depression in the elderly. DESIGN: A randomized double-blind parallel study with 6 weeks of follow-up. SETTING: The psychogeriatric clinic at the Institute of Psychiatry, Hospital das Clínicas, Faculty of Medicine of the University of São Paulo. PARTICIPANTS: 55 severe and moderately depressed non-demented outpatients aged 60 years or more. INTERVENTION: Patients were assigned to sertraline 50 mg/day or imipramine 150 mg/day. MAIN MEASUREMENTS: CAMDEX interview. Psychiatric diagnosis followed the guidelines for "Major Depressive Episode" according to DSM-IV criteria. Severity of symptoms was evaluated using the "CGI" and "MADRS" scales. Cognitive state was assessed using the Mini-Mental State Examination. Side effects were assessed using the "Safetee-Up" schedule. RESULTS: Both groups had a significant decrease in depressive symptoms according to the MADRS scores after 6 weeks of treatment (P = 0.01). No significant differences between groups were detected regarding treatment outcome (t = 0.4; P = 0.7). Although the dropout rate was greater in the imipramine group, the overall tolerability among patients who completed the 6-week trial was similar in both test groups. CONCLUSIONS: Both sertraline and imipramine exhibited good efficacy and an acceptable side-effect profile for elderly depressed patients after 6 weeks of antidepressant treatment.